Influence of Cognitive Stimulation Group Activity Memory Game Therapy on Elderly Cognitive Function: Quasi-Experimental - Qolbi Nur Qoidah Yahya; Purwaningsih Purwaningsih; Makhfudli Makhfudli (Universitas Airlangga, 2019)
Introduction: Older adults experience a change in their nervous system that influences cognitive function, including the abilities of orientation, registration, attention-calculation, memory and language. These changes affect the independence of the elderly when carrying out their daily activities. The purpose of this research was to analyze the effect of cognitive stimulation group activity memory game therapy on elderly cognitive function.Methods: This study used a quasi-experimental pre-post approach with a control group design. The population in this study was the elderly who were aged >60 in Nursing Home Blitar, totaling 20 older patients. The data retrieval for this research was conducted between April and May 2012. The elderly in the treatment group were given flash card stimulus to practice their perceptual abilities 8 times (1 month). The measurement of elderly cognitive function used the Mini Mental State Examination questionnaire. The data was analyzed using the Wilcoxon Sign Rank test.Results: The results showed that elderly cognitive function increased from 10,3 (pre test) to 14,65 (post test) with p=0,005 (p<0,05). This result shows that cognitive stimulation group activity memory games have a significance influence on elderly cognitive function.Conclusion: Practical nurses can use this therapy to improve elderly cognitive function not only in Elderly Social Institutions but also in the community or through public health.